Intra - Abdominal Sertoli Cell Tumour in a Dog and its Surgical Management - Gokulakrishnan, M.; Nagarajan, L.; Ali, Mohamed; Meena, Jothi (International Journal of Livestock Research, 2020)
A 11-year-old intact male dog was brought to Madras Veterinary College Teaching Hospital with a history of alopecia, hyperpigmentation, cryptorchid and anorexia. Haemato-biochemical analysis was done, which revealed thrombocytopenia, neutrophilia shift to left and a marginal increase in ALP levels. Soft contoured mass was observed on lateral abdominal radiograph with absence of metastasis. Ultrasound guided biopsy was made to rule out the nature of tumour cells that confirmed intra-abdominal sertoli cell tumour. An exploratory laparotomy was made and intra- abdominal testicle was excised and removed. The intra scrotal testicle which was atrophied was resected following which a scrotal ablation was made. The animal was reviewed after a month which revealed reduction in alopecia, hyperpigmentation and uneventful recovery.